Adhesive structure and method for manufacturing adhesive structure

JP2025042250APending Publication Date: 2025-03-27MITSUBISHI MATERIALS CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023149145
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-14
Publication Date
2025-03-27

AI Technical Summary

Benefits of technology

【0019】 本発明によれば、高温環境下およびクリーン環境下でも安定して使用可能であり、十分な接着力を得ることが可能な接着構造体、および、接着構造体の製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025042250000001_ABST
    Figure 2025042250000001_ABST
Patent Text Reader

Abstract

To provide an adhesive structure that can be stably used even in a high-temperature environment and a clean environment and can achieve sufficient adhesive force.SOLUTION: Provided is an adhesive structure in which a fiber structure layer configured from a plurality of fiber bodies composed of an inorganic material is formed on at least a portion of the surface of a base material composed of an inorganic material, the equivalent circle diameter D of a cross-section orthogonal to the extension direction of a fiber body 21 constituting the fiber structure layer is within the range of 15-400 nm, and an aspect ratio H / D calculated from the height H and the equivalent circle diameter D of the fiber body 21 is 3 or greater.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesive structure. [Background technology]

[0002] For example, in semiconductor manufacturing equipment, if particles or the like are present on the surface that holds a semiconductor wafer, the flatness of the surface will be impaired, causing manufacturing defects and reducing yields. Conventionally, as a method for removing particles, for example, as shown in Patent Documents 1 and 2, a substrate to which an adhesive substance is adhered is used as a cleaning wafer, and this cleaning wafer is transported idly to remove particles in the transport system and processing unit.

[0003] In addition, in the case of a gripping member that grips an object and a transporting member that transports an object, as shown in Patent Documents 2 and 3, for example, an adhesive structure having adhesive properties is arranged in the portion that comes into contact with the object in order to stably fix the object. Furthermore, when handling an object, for example, as shown in Patent Document 4, an adhesive structure having adhesiveness is used to temporarily fix the object and prevent it from shifting position. Here, since the bonded structure is required to have a sufficient frictional force between itself and the object, it is usually made of an organic material such as rubber, which is a viscoelastic body. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2009-117440 A [Patent Document 2] JP 2018-094704 A [Patent Document 3] WO2009 / 005027 publication [Patent Document 4] JP 2009-168860 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, in the method disclosed in Patent Document 1, it is necessary to temporarily stop the operation of the semiconductor manufacturing equipment or to lower the environmental temperature to 400° C. or lower when removing particles, and the downtime causes a problem of reduced productivity. In addition, organic materials such as rubber have problems in that they cannot be used stably in high-temperature environments due to insufficient heat resistance, and they cannot be used in clean environments due to the risk of contamination by the organic materials. Therefore, for example, bonded structures made of organic materials could not be applied to semiconductor manufacturing process applications, aerospace applications, and robot applications.

[0006] Here, the industrial materials constituting the various members are roughly divided into organic materials such as resin and rubber, and inorganic materials such as ceramics and metals. As mentioned above, organic materials have excellent flexibility but poor heat resistance. In contrast, inorganic materials have excellent heat resistance but poor flexibility. Thus, when it comes to industrial materials, a trade-off in properties occurs depending on the material selected.

[0007] For this reason, when the adhesive structure is made of an inorganic material, it has excellent heat resistance and reduces contamination problems, but there is a risk that it is not possible to obtain sufficient adhesive strength, and it is not possible to adequately fix the object or to adsorb and remove particles.

[0008] The present invention has been made in consideration of the above-mentioned circumstances, and has an object to provide an adhesive structure that can be used stably even in high-temperature environments and clean environments and that can obtain sufficient adhesive strength. [Means for solving the problem]

[0009] In order to solve this problem, the inventors conducted extensive research and discovered that by forming a special structure on the surface of a substrate made of an inorganic material such as ceramics or metal, sufficient adhesive strength can be imparted to the surface, making it possible to use the substrate as an adhesive structure.

[0010] The present invention has been made based on the above-mentioned findings, and the adhesive structure of aspect 1 of the present invention is characterized in that a fiber structure layer composed of a plurality of fiber bodies made of an inorganic material is formed on at least a portion of the surface of a substrate made of an inorganic material, and the circular equivalent diameter D of a cross section perpendicular to the extension direction of the fiber bodies constituting the fiber structure layer is within a range of 15 nm or more and 400 nm or less, and the aspect ratio H / D calculated from the circular equivalent diameter D and height H of the fiber bodies is 3 or more.

[0011] According to the bonded structure of the first aspect of the present invention, since it is made of an inorganic material such as ceramics or metal, it has excellent heat resistance and can sufficiently suppress the problem of contamination. Furthermore, a fiber structure layer consisting of a plurality of fiber bodies is formed on at least a portion of the surface of the substrate, the circular equivalent diameter D of a cross section perpendicular to the extension direction of the fiber bodies is within a range of 15 nm or more and 400 nm or less, and the aspect ratio H / D calculated from the circular equivalent diameter D and height H of the cross section of the fiber bodies is 3 or more, so that it is possible to impart sufficient adhesive strength to the surface of the substrate. Therefore, it can be used stably even in high-temperature and clean environments, and sufficient adhesive strength can be obtained. That is, the bonded structure of the first aspect of the present invention can be used as an anti-slip member or a foreign matter adsorbing member that can be used stably even in high-temperature and clean environments.

[0012] The bonded structure of a second aspect of the present invention is the bonded structure of the first aspect, characterized in that the fibrous bodies constituting the fiber structure layer are made of a metal oxide. According to the adhesive structure of aspect 2 of the present invention, the fibrous bodies constituting the fiber structure layer are made of metal oxide, so that the fiber structure layer can be reliably formed in the above-mentioned shape, sufficient adhesive strength can be obtained, and the heat resistance is excellent, and contamination problems can be sufficiently suppressed.

[0013] The bonded structure of a third aspect of the present invention is characterized in that in the bonded structure of the second aspect, the metal oxide is aluminum oxide. According to the adhesive structure of aspect 3 of the present invention, the fibrous bodies constituting the fiber structure layer are made of aluminum oxide, and therefore sufficient adhesive strength can be obtained, while the heat resistance is excellent and contamination problems can be sufficiently suppressed.

[0014] The bonded structure of embodiment 4 of the present invention is characterized in that in the bonded structure of any one of embodiments 1 to 3, the occupancy rate of the fiber structure layer on the surface is 20% or more. According to the adhesive structure of aspect 4 of the present invention, the occupancy area ratio of the fiber structure layer on the surface is 20% or more, so that sufficient adhesive strength can be reliably obtained and particles can be reliably removed.

[0015] The bonded structure of embodiment 5 of the present invention is characterized in that in the bonded structure of any one of embodiments 1 to 4, the adsorption rate of particles having a particle diameter of 1 μm or more and 30 μm or less is 5% or more. According to the bonded structure of the fifth aspect of the present invention, the adsorption rate of particles having a particle diameter of 1 μm or more and 30 μm or less is 5% or more, so that the particles can be reliably adhered and removed.

[0016] The bonded structure of a sixth aspect of the present invention is the bonded structure of any one of the first to fifth aspects, characterized in that the static friction coefficient of the surface of the substrate against silicon is 0.30 or more. According to the bonded structure of the sixth aspect of the present invention, the static friction coefficient of the surface of the base material against silicon is set to 0.30 or more, so that the target member can be reliably fixed.

[0017] The bonded structure of aspect 7 of the present invention is a method for manufacturing a bonded structure according to any one of claims 1 to 6, comprising a pretreatment step of forming a mirror-finished metal surface on the surface of the base material, an anodizing step of anodizing the metal surface, and an etching step of dissolving and removing a portion of the resulting anodized layer, characterized in that the anodizing step and the etching step are repeated multiple times.

[0018] According to the bonded structure of the seventh aspect of the present invention, the mirror-finished metal surface is repeatedly anodized and etched, so that the above-mentioned fiber structure layer can be formed on the surface of the substrate, which allows the manufacture of a bonded structure that can be stably used even in high-temperature and clean environments and has sufficient adhesive strength. Effect of the Invention

[0019] According to the present invention, it is possible to provide a bonded structure that can be stably used even in high-temperature environments and clean environments and that can obtain sufficient adhesive strength, and a method for manufacturing the bonded structure. [Brief description of the drawings]

[0020] [Figure 1] 1 is a schematic explanatory diagram of an adhesive structure according to an embodiment of the present invention; [Diagram 2] 1 is an explanatory diagram of a fiber structure layer in an adhesive structure according to one embodiment of the present invention, where (a) is an SEM observation photograph and (b) is a schematic diagram. [Diagram 3] 1 is an explanatory diagram of a fiber structure layer in an adhesive structure according to one embodiment of the present invention, where (a) is an SEM observation photograph and (b) is a schematic diagram. [Figure 4] FIG. 2 is an explanatory diagram of a fibrous body in a bonded structure according to one embodiment of the present invention. [Diagram 5] FIG. 2 is an explanatory diagram showing a method for measuring a particle adsorption rate. [Figure 6] FIG. 2 is an explanatory diagram showing a method for measuring a static friction coefficient. [Figure 7] FIG. 2 is a flow diagram showing a method for manufacturing a bonded structure according to the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] Hereinafter, an adhesive structure 10 according to one embodiment of the present invention will be described with reference to the accompanying drawings. The adhesive structure 10 of this embodiment is used, for example, in gripping devices, conveying devices, manufacturing devices, etc. that are used in high temperature or clean environments in the aerospace field, semiconductor manufacturing process field, medical field, etc., to temporarily fix objects or adsorb and remove particles present on the surface of a substrate, etc.

[0022] The bonded structure 10 of this embodiment has a substrate 11 made of an inorganic material such as ceramics or metal, and a fiber structure layer 20 made of a plurality of fiber bodies 21 is formed on at least a portion of the surface of the substrate 11. There is no particular restriction on the shape or size of the base material 11, but in this embodiment, as shown in FIG. 1, it is in the form of a plate, and its thickness is within the range of, for example, 10 μm or more and 10 cm or less.

[0023] Here, examples of inorganic materials constituting the base material 11 include metals, ceramics, silicon, and glass. The inorganic material constituting the base material 11 preferably has a melting point of 100° C. or higher and a decomposition temperature of 100° C. or higher, more preferably has a melting point of 300° C. or higher and a decomposition temperature of 300° C. or higher, and even more preferably has a melting point of 500° C. or higher and a decomposition temperature of 500° C. or higher.

[0024] The metal constituting the substrate 11 may be a simple metal or an alloy. Alloys include those made of a plurality of metal elements and those made of a metal element and a nonmetal element. Examples of simple metals include aluminum, nickel, iron, copper, titanium, tungsten, and magnesium. Examples of alloys include aluminum alloys, NiP, stainless steel, and copper alloys.

[0025] Oxides, nitrides, and carbides can be used as the ceramics constituting the base material 11. Examples of ceramics include aluminum oxide (alumina), titanium oxide, and quartz. The inorganic material constituting the substrate 11 is preferably a metal, and more preferably contains any of copper, a copper alloy, aluminum, an aluminum alloy, and a NiP alloy.

[0026] The fiber structure layer 20 formed on the surface of the substrate 11 has a structure in which a plurality of fiber bodies 21 are arranged upright, as shown in FIG. 2 or FIG. Here, the metal oxide constituting the fibrous body 21 is preferably aluminum oxide. In this embodiment, the base material 11 is made of aluminum, and the fibrous body 21 is made of aluminum oxide.

[0027] The fibrous body 21 has an average circle-equivalent diameter D of a cross section perpendicular to its extending direction in the range of 15 nm to 400 nm. The circle-equivalent diameter D of the fibrous body 21 can be measured from a cross-sectional SEM photograph of the fiber structure layer 20 taken with a SEM (scanning electron microscope). In this embodiment, the fibrous body 21 has a roughly cone shape as shown in Fig. 4, and the circle-equivalent diameter D is the circle-equivalent diameter of the cross section of the bottom of the cone shape. Here, the lower limit of the average value of the equivalent circle diameter D of the cross section of the fibrous body 21 is more preferably 30 nm or more, and even more preferably 50 nm or more. On the other hand, the average value of the equivalent circle diameter D of the cross section of the fibrous body 21 is preferably 300 nm or less, and even more preferably 200 nm or less.

[0028] Moreover, the aspect ratio H / D of the fibrous body 21, calculated from the average value of the equivalent circle diameters D and the average height H of the fibrous body 21, is preferably 3 or more. The aspect ratio of the fibrous body 21 can be measured from a cross-sectional SEM photograph of the fiber structure layer 20 taken with a SEM (scanning electron microscope). The aspect ratio H / D of the fibrous body 21 is preferably 4 or more, and more preferably 5 or more. On the other hand, the aspect ratio H / D of the fibrous body 21 is preferably 50 or less, and more preferably 30 or less.

[0029] The average height H of the fibrous body 21 is preferably within a range of 50 nm to 3000 nm. The height of the fibrous body 21 can be measured from a cross-sectional SEM photograph of the fiber structure layer 20 taken with a SEM (scanning electron microscope). The average height H of the fibrous body 21 is preferably 300 nm or more, more preferably 500 nm or more, while the average height H of the fibrous body 21 is preferably 3000 nm or less, more preferably 2000 nm or less.

[0030] In the bonded structure 10 of this embodiment, the area ratio (occupancy rate) of the fiber structure layer 20 on the surface (bonded surface) is preferably 20% or more. In the bonded structure 10 shown in FIG. 1, the fiber structure layer 20 is formed on approximately 70% of the surface of the substrate 11 . The area ratio of the fiber structure layer 20 to the surface of the base material 11 is preferably 25% or more, and more preferably 50% or more. Also, the area ratio of the fiber structure layer 20 to the surface of the base material 11 is 100% or less.

[0031] In the bonded structure 10 of this embodiment, the adsorption rate of particles having a particle diameter of 1 μm or more and 30 μm or less is set to 5% or more. Here, the particle adsorption rate can be calculated by the procedure shown in Fig. 5. That is, a liquid containing particles with a particle diameter of 1 µm to 30 µm (PSL particles: polystyrene latex particles) is dropped onto the surface of the object to disperse the particles. The surface of the bonded structure 10 on which the fiber structure layer 20 is formed is brought into contact with the object to adsorb the particles. The number of particles in the contact area of ​​the bonded structure 10 on the surface of the object before and after contact with the bonded structure 10 is counted, and the particle adsorption rate is calculated.

[0032] In the bonded structure 10 of this embodiment, the static friction coefficient μ of the surface of the substrate 11 on which the fiber structure layer 20 is formed is set to 0.30 or more. The static friction coefficient μ on the surface of the substrate 11 is preferably 0.35 or more, and more preferably 0.40 or more. There is no particular upper limit to the static friction coefficient μ, but in reality, the static friction coefficient μ is 10 or less. Here, the static friction coefficient μ on the surface of the substrate 11 can be calculated by the formula shown in Fig. 6. In Fig. 6, m is the mass of the object, g is the gravitational acceleration, F0 is the maximum static friction force, and N is the normal force. Specifically, when the angle at which sliding begins is θ, the static friction coefficient μ is expressed as μ=tan θ.

[0033] Next, a description will be given of an example of a method for manufacturing the bonded structure 10 of this embodiment. In the bonded structure 10 of this embodiment, as described above, the base material 11 is made of aluminum, and the fibrous body 21 is made of aluminum oxide. As shown in the flow diagram of FIG. 7, this embodiment includes a pretreatment step S01, an anodization step S02, and an etching step S03.

[0034] In the pretreatment step S01, a mirror-finished metal surface is formed on the surface of the base material 11. In this embodiment, since the base material 11 is made of aluminum, the surface of the base material 11 is electrolytically polished to give it a mirror finish, thereby forming a mirror-finished metal surface. In this embodiment, the substrate 11 is immersed in an electropolishing solution (for example, HClO4 / EtOH) at a temperature of 0° C. to 5° C. for a retention time of 4 minutes to 5 minutes, and a current density of 0.20 A / cm 2 More than 0.25A / cm 2 Electrolytic polishing is carried out under the following conditions:

[0035] In the anodization step S02, the metal surface formed in the pretreatment step S01 is anodized. An anodization film is formed by the anodization. In this embodiment, the anodization is performed using a treatment liquid (for example, an aqueous H3PO4 solution) under conditions of a temperature of 0° C. to 5° C., a holding time of 60 minutes to 70 minutes, and a voltage of 160V to 170V.

[0036] In the etching step S03, a part of the anodized layer obtained in the anodizing step S02 is dissolved and removed. In this embodiment, the etching process is performed using an etching solution (for example, H2CrO4 / HPO4 aqueous solution or H3PO4 aqueous solution) at a temperature of 70° C. to 75° C. for a retention time of 120 minutes to 130 minutes.

[0037] Here, the above-mentioned anodizing step S02 and etching step S03 are repeatedly performed, thereby forming a fiber structure layer 20 having a plurality of fiber bodies 21 standing upright. By adjusting the number of times the anodizing step S02 and the etching step S03 are repeated, it is possible to manufacture the fiber structure layer 20 having the structure shown in FIG. 2 or the fiber structure layer 20 having the structure shown in FIG.

[0038] The bonded structure 10 of this embodiment is manufactured by the above-mentioned steps.

[0039] The adhesive structure 10 of this embodiment configured as described above is made of inorganic materials such as ceramics and metals, and therefore has excellent heat resistance and can sufficiently suppress contamination problems. A fiber structure layer 20 consisting of a plurality of fiber bodies 21 is formed on at least a part of the surface of the base material 11, and the fiber structure layer 20 has a cross section perpendicular to the extending direction of the fiber bodies 21 having a circle-equivalent diameter D in the range of 15 nm to 400 nm, and an aspect ratio H / D calculated from the circle-equivalent diameter D and height H of the fiber bodies 21 is 3 or more, so that it is possible to impart a sufficient adhesive strength to the surface of the base material 11. This allows stable use even in high-temperature and clean environments, and makes it possible to obtain a sufficient adhesive strength.

[0040] In the adhesive structure 10 of this embodiment, when the fiber body 21 constituting the fiber structure layer 20 is composed of a metal oxide, the fiber structure layer 20 composed of the fiber body 21 of the above-mentioned configuration can be reliably formed, sufficient adhesive strength can be obtained, and the heat resistance is excellent, and contamination problems can be sufficiently suppressed.

[0041] In the adhesive structure 10 of this embodiment, when the metal oxide constituting the fibrous body 21 is composed of aluminum oxide, a suitable fiber structure layer 20 can be formed to obtain sufficient adhesive strength.

[0042] In the bonded structure 10 of this embodiment, when the area ratio of the fiber structure layer 20 on the surface of the substrate 11 is 20% or more, the fiber structure layer 20 can reliably obtain a sufficient adhesive strength.

[0043] In the bonded structure 10 of this embodiment, when the adsorption rate of particles having a particle diameter of 1 μm or more and 30 μm or less is 5% or more, particles present on the surface of an object can be reliably adhered and removed.

[0044] In the bonded structure 10 of this embodiment, if the static friction coefficient of the surface of the base material 11 against silicon is 0.30 or more, the bonded structure 10 can be used to reliably fix a target member.

[0045] In the manufacturing method of the bonded structure 10 of this embodiment, a mirror-finished metal surface is formed on the surface of the base material 11, and this metal surface is repeatedly subjected to anodizing and etching, so that the above-mentioned fiber structure layer 20 can be formed on the surface of the base material 11. This makes it possible to manufacture a bonded structure 10 that can be stably used even in high-temperature and clean environments and that can obtain sufficient adhesive strength.

[0046] Although the bonded structure according to the embodiment of the present invention has been described above, the present invention is not limited thereto, and can be modified as appropriate without departing from the technical concept of the invention. For example, in this embodiment, the substrate is described as being aluminum and the fibrous body constituting the fiber structure layer is formed from aluminum oxide, but this is not limited to this, and the substrate and fibrous body may be made of other inorganic materials. EXAMPLES

[0047] The results of experiments carried out to confirm the effects of the present invention will be described below.

[0048] (Example 1 of the present invention) First, a substrate (length: 7 mm, width: 7 mm, thickness: 1 mm) made of an inorganic material shown in Table 1 was prepared. The substrate was electrolytically polished using a 20 vol% HClO4 / 80 vol% EtOH solution at a current density of 0.2 A / cm 2 Electrolytic polishing was performed at a temperature of 0°C for a treatment time of 4 minutes to give a mirror finish to the surface of the substrate.

[0049] The obtained sample was anodized for 120 minutes in a 0.2 M malic acid aqueous solution containing 3 mM phosphoric acid at a bath temperature of 16°C and at a constant voltage of 350 V. After anodization, the plate was immersed in an aqueous solution containing 1.8 mass% chromic acid and 6 mass% phosphoric acid at a bath temperature of 70°C for 2 hours to selectively dissolve and remove only the anodized layer, yielding an aluminum plate with a recessed pattern corresponding to the arrangement of pores on the back side of the anodized film.

[0050] Using the aluminum plate having the dimple pattern, anodization was again carried out for 35 seconds under the same conditions as the previous anodization. The obtained sample was etched in a 10 mass% aqueous phosphoric acid solution at a bath temperature of 30° C. for 16 minutes. By repeating five sets of anodization and etching, a pillar array structure with a diameter of 15 nm and a height of 50 nm was obtained.

[0051] (Example 2 of the present invention) A substrate (length: 7 mm, width: 7 mm, thickness: 1 mm) made of the inorganic material shown in Table 1 was prepared. The substrate was electrolytically polished using a 20 vol% HClO4 / 80 vol% EtOH solution at a current density of 0.2 A / cm 2 Electrolytic polishing was performed at a temperature of 0°C for a treatment time of 4 minutes to give a mirror finish to the surface of the substrate.

[0052] The electrolytically polished sample was anodized using a 0.1 mol H3PO4 aqueous solution under conditions of a voltage of 160 V, a temperature of 0°C, and a treatment time of 60 minutes. Next, the plate was etched using a 1.8 mass% HCrO4 / 6.0 mass% HPO4 aqueous solution at 70°C for 120 minutes to remove part of the anodized film, yielding an aluminum plate with a recess pattern corresponding to the arrangement of the pores on the back side of the anodized film.

[0053] An aluminum plate with a recess pattern was anodized using a 0.1 mol H3PO4 aqueous solution at a voltage of 160 V, a temperature of 0°C, and a treatment time of 60 minutes, and then etched using a 10 mass% H3PO4 aqueous solution at a temperature of 30°C and a treatment time of 160 minutes to form an alumina pillar array structure.

[0054] (Example 3 of the present invention) The electrolytically polished sample was subjected to the same procedure as in Invention Example 2, except that the anodization voltage was set to 250 V, to obtain a pillar array structure having a diameter of 200 nm and a height of 1000 nm.

[0055] (Example 4 of the present invention) The electrolytically polished sample was subjected to the same procedure as in Invention Example 2, except that the anodization voltage was set to 350 V, to obtain a pillar array structure having a diameter of 300 nm and a height of 1200 nm.

[0056] (Example 5 of the invention) The electrolytically polished sample was subjected to the same procedure as in Invention Example 2, except that the anodization voltage was set to 130 V, to obtain a pillar array structure having a diameter of 72 nm and a height of 611 nm.

[0057] (Example 6) The electrolytically polished sample was subjected to the same procedure as in Invention Example 2, except that the anodization voltage was set to 100 V, to obtain a pillar array structure having a diameter of 91 nm and a height of 23,300 nm.

[0058] Comparative Example 1 First, a substrate (length: 7 mm, width: 7 mm, thickness: 1 mm) made of an inorganic material shown in Table 1 was prepared. The substrate was electrolytically polished using a 20 vol% HClO4 / 80 vol% EtOH solution at a current density of 0.2 A / cm 2 Electrolytic polishing was performed at a temperature of 0°C for a treatment time of 4 minutes to obtain an aluminum mirror surface.

[0059] Comparative Example 2 The same operations as in Example 1 of the present invention were carried out except that the etching using the aluminum plate having a dent pattern was carried out for 25 minutes, thereby obtaining a pillar array structure having a diameter of 10 nm and a height of 35 nm.

[0060] Comparative Example 3 The same operations as in Example 1 of the present invention were carried out except that the etching using the aluminum plate having a dent pattern was carried out for 9 minutes, thereby obtaining a pillar array structure having a diameter of 25 nm and a height of 30 nm.

[0061] Comparative Example 4 The same operations as in Example 1 of the present invention were carried out except that the etching using the aluminum plate having a dent pattern was carried out for 5 minutes, thereby obtaining a pillar array structure having a diameter of 50 nm and a height of 100 nm.

[0062] For the bonded structure obtained as described above, the particle adsorption rate was measured by the following procedure.

[0063] A 300 mm disk-shaped silicon wafer S was prepared. A liquid containing standard particles with an average particle diameter of 30 μm was dropped onto the surface of the silicon wafer to disperse the standard particles. In this state, the number of particles present in the area where the adhesive structure was to be laminated on the surface of the silicon wafer was measured using a particle counter. Next, the adhesive structure and the silicon wafer were stacked so that the surface of the above-mentioned adhesive structure on which the tube array structure was formed was in contact with the surface of the silicon wafer S on which standard particles (polystyrene latex particles: 30 μm) were dispersed, and after keeping them in contact for 30 seconds, the adhesive structure was removed.

[0064] The number of particles present on the surface of the silicon wafer in the area where the adhesive structure was laminated was measured using a particle counter. The particle adsorption rate was calculated from the number of particles before and after laminating the adhesive structure. The results are shown in Table 1.

[0065] [Table 1]

[0066] In Comparative Example 1 in which a fiber structure layer was not formed, and in Comparative Examples 2 to 4 in which the circular equivalent diameter D of the cross section of the fibrous body and the aspect ratio H / D of the circular equivalent diameter D to the height H were outside the range of the present invention, the particle adsorption rate was 0.0%, and no effect of removing particles was observed.

[0067] In contrast, in Examples 1 to 6 of the present invention, a fiber structure layer was formed in which the circular equivalent diameter D of the cross section of the fibrous body and the aspect ratio H / D of the circular equivalent diameter D were within the range of the present invention, the particle adsorption rate was 5% or more, and it was confirmed that particles present on the surface of the target object could be removed.

[0068] From the above, it was confirmed that the present invention can provide an adhesive structure that can be stably used even in high temperature and clean environments and that can obtain sufficient adhesive strength. [Explanation of symbols]

[0069] 10 Adhesive structure 11 Base material 20 Fiber structure layer 21 Fibrous bodies

Claims

1. a fiber structure layer made of a plurality of fiber bodies made of an inorganic material is formed on at least a part of a surface of a base material made of an inorganic material; An adhesive structure, characterized in that the circular equivalent diameter D of a cross section perpendicular to the extension direction of the fibrous body constituting the fiber structure layer is in the range of 15 nm to 400 nm, and the aspect ratio H / D calculated from the circular equivalent diameter D and height H of the fibrous body is 3 or more.

2. The adhesive structure according to claim 1 , wherein the fibrous bodies constituting the fiber structure layer are made of a metal oxide.

3. The bonded structure according to claim 2, wherein the metal oxide is aluminum oxide.

4. 2. The adhesive structure according to claim 1, wherein the occupancy rate of the fiber structure layer on the surface is 20% or more.

5. 2. The bonded structure according to claim 1, wherein the adsorption rate of particles having a particle diameter of 1 μm or more and 30 μm or less is 5% or more.

6. 2. The bonded structure according to claim 1, wherein the static friction coefficient against silicon is 0.30 or more.

7. A method for producing the bonded structure according to any one of claims 1 to 6, comprising the steps of: A method for manufacturing an adhesive structure, comprising: a pretreatment step of forming a mirror-finished metal surface on the surface of the base material; an anodization step of anodizing the metal surface; and an etching step of dissolving and removing a portion of the anodized layer obtained, the method being characterized in that the anodization step and the etching step are repeated multiple times.

Citation Information

Patent Citations

  • Cleaning wafer

    JP2009117440A

  • Stage device for substrate

    JP2009168860A

  • Gripper to be mounted on robot

    JP2018094704A

  • Substrate transfer robot and vacuum processing apparatus provided with the same

    WO2009005027A1